2012
DOI: 10.1016/j.jvs.2011.10.128
|View full text |Cite
|
Sign up to set email alerts
|

Results for primary bypass versus primary angioplasty/stent for intermittent claudication due to superficial femoral artery occlusive disease

Abstract: Background Percutaneous transluminal angioplasty +/− stent (PTA/S) and surgical bypass are both accepted treatments for claudication due to superficial femoral artery (SFA) occlusive disease. However, long-term results comparing these modalities for primary intervention in patients who have had no prior intervention has not been reported. We report our results with three year follow-up. Methods We reviewed all lower extremity bypass procedures at Beth Israel Deaconess Medical Center from 2001–2009 and all PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 30 publications
5
88
1
1
Order By: Relevance
“…It has been reported that statin therapy is associated with improved infrainguinal autogenous venous graft patency, with a 3.2‐fold increased risk of graft failure in patients not on statins 52. Additionally, statin therapy is associated with reduced restenosis rates after endovascular intervention,53, 54 and reduced rates of symptom recurrence after revascularization for intermittent claudication 54. Aiello et al showed in a retrospective study in 646 CLI patients that statins can improve limb salvage rates after endovascular interventions for CLI (limb salvage 83% versus 62% at 24 months) 55.…”
Section: Trends In Medical Therapy For Padmentioning
confidence: 99%
“…It has been reported that statin therapy is associated with improved infrainguinal autogenous venous graft patency, with a 3.2‐fold increased risk of graft failure in patients not on statins 52. Additionally, statin therapy is associated with reduced restenosis rates after endovascular intervention,53, 54 and reduced rates of symptom recurrence after revascularization for intermittent claudication 54. Aiello et al showed in a retrospective study in 646 CLI patients that statins can improve limb salvage rates after endovascular interventions for CLI (limb salvage 83% versus 62% at 24 months) 55.…”
Section: Trends In Medical Therapy For Padmentioning
confidence: 99%
“…There are not many publications comparing femoral artery stenting and bypass surgery, and the assessment of patency and the overall results of different treatment modalities is somewhat problematic, as study designs vary considerably. [16][17][18][19] In our series, 80% of TASC II A and B lesions received stents and 76% of TASC II C and D lesions received bypasses. These figures are in keeping with those reported in previous studies.…”
Section: Discussionmentioning
confidence: 59%
“…These figures are in keeping with those reported in previous studies. 9,18,19 There is evidence that shorter lesions do well with angioplasty/ stent, while longer lesions have significantly lower patency rates. 9 The latest TASC II recommendations include an endovascular approach for shorter lesions and a bypass for longer lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies stated that the primary patency rate of bypass surgery was considerably higher than endovascular treatment in femoropopliteal arterial diseases [12,13]. The endovascular treatment can be the first choice in the case of poor condition [14].…”
Section: Discussionmentioning
confidence: 99%